2018
DOI: 10.1016/j.ajpath.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Cavity Types and Evidence that Mechanical Action on the Necrotic Granuloma Drives Tuberculous Cavitation

Abstract: Effacement of normal lung parenchyma by cavities is an important sequela of pulmonary tuberculosis. Despite its clinical significance, the pathogenesis of tuberculous cavitation is poorly understood, with controversy as to whether the fundamental mechanism involves matrix depletion, lipid pneumonia, or mechanical factors. In this study, a repetitive aerosol infection model using Mycobacterium tuberculosis was used to generate cavities in 20 New Zealand white rabbits. Serial computed tomography was performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Third, the alveolar spaces in the lesions expanded to reduce the tissue defects after a subsequent spontaneous resolution. In our case, the formation of thin-walled cysts might have been associated variably with a mechanism similar to that proposed by Ihms et al [ 14 ]. Additionally, the severe tissue-damaging inflammation might have led to the continuous accumulation of leaked air in the tissue defects, leading to pulmonary pneumatoceles [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Third, the alveolar spaces in the lesions expanded to reduce the tissue defects after a subsequent spontaneous resolution. In our case, the formation of thin-walled cysts might have been associated variably with a mechanism similar to that proposed by Ihms et al [ 14 ]. Additionally, the severe tissue-damaging inflammation might have led to the continuous accumulation of leaked air in the tissue defects, leading to pulmonary pneumatoceles [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 82%
“…The patient presented with an eosinophilic lung disease that manifested clinically as the formation of multiple cysts, which resolved spontaneously. In a high-resolution CT and histopathological analysis of a rabbit model of tuberculous cavities, Ihms et al reported that all cavities were pathologically associated with the central necrotic areas of granulomas and that a certain level of communication was observed between the cavities and respiratory tract [ 14 ]. Based on the results, they proposed the following mechanisms of thin-walled cavity formation and progression: 1) with inspiration, external tension in the surrounding lung tissue pulls air into the necrotic center, 2) if the outlet is severely obstructed creating a ball-valve effect, extreme air trapping occurs and causes the cavity to assume a thin-walled morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were infected by Mtb H37Rv using a Glas-Col chamber, and mice were sacrificed for enumeration of Mtb CFU in lungs and spleen day 1 counts as well as subsequent time points as previously described (67). H&E stained tissue sections were imaged by high resolution digital microscopy and lesion scoring was performed as described (68). High resolution PET/CT imaging was conducted using a Mediso nanoScan instrument.…”
Section: Animal Infections and Imagingmentioning
confidence: 99%
“…Mice were infected by Mtb H37Rv using a Glas-Col chamber, and mice were sacrificed for enumeration of Mtb CFU in lungs and spleen day 1 counts as well as subsequent time points as previously described 86 . H&E stained tissue sections were imaged by high resolution digital microscopy and lesion scoring was performed as described 87 . High resolution PET/CT imaging was conducted using a Mediso nanoScan instrument.…”
Section: Animal Infections and Imagingmentioning
confidence: 99%